The effect of hypnobreastfeeding on breast milk expenditure in postpartum mothers primiparous days 4-7 in TPMB Heni Nurhaeni Bandung city year 2024 - Nurhayati, Fitri; Irianto, Gunawan; Yulianah, Regina (Institute of Computer Science (IOCS), 2024)
Decreased breast milk expenditure caused by physical and emotional stress, stressful events are very vulnerable to be experienced by primiparous mothers because of the first experience in caring for and providing exclusive breastfeeding. One of the nonpharmacological efforts to deal with disorders in breast milk production is hypnobreastfeeding, by giving positive suggestions when the mother is in a relaxed state. The purpose of this study is to determine the effect of hypnobreastfeeding on breast milk expenditure in postpartum mothers Primipara days 4-7 at TPMB Heni Nurhaeni Bandung City in 2024. The type of research used is pre-experimental designs with one group pretest-posttest design. The sample of this study was 34 postpartum mothers primipara days 4-7 in January 2024 at TPMB Heni Bandung City. Data collection using observation sheets of breast milk expenditure, data analysis using univariate analysis and bivariate analysis namely Wilcoxon Test. The results of the study stated that before the intervention, the average milk expenditure was 60 ml and after the intervention was 95 ml, and there was an influence of hypnobreastfeeding techniques on breast milk expenditure in primiparous postpartum mothers days 4-7 (p value 0.000). The conclusion of this study is that there is an effect of hypnobreastfeeding on breast milk expenditure in postpartum mothers primiparous days 4-7 at TPMB Heni Nurhaeni in Bandung City in 2024. Advice for midwives, hypnobreastfeeding can be used as a natural effort to increase breast milk expenditure in postpartum mothers.